Novel of Ideas A Textual Analysis of Mohd. Affandi Hasan's Pujangga Melayu Base on Persuratan Baru - Mohd. Zariat Abdul Rani (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
The function of literary works, specifically that of fictional narratives, has beensource of debate in Western and Eastern civilisations throughout the ages. TheMalay literary tradition is no exception; V.1. Braginsky states that since the 16thand 17th centuries, Malays have been aware of the functional value of Iiterature,which among other functions serves to teach, and to enlighten mankind withknowledge. It is important to note that the same issue is still a matter of debatein contemporary Malay literature. Chief amongst those who regularly foregroundthe issue is Mohd. Affandi Hassan (heralter Hassan), a contemporary Malayliterary critic and creative writer. As a literary critic, Hassan generated the notion of 'Persuratan Baru', a notion that amongst other principles urges authorsif Malay literary works to prioritise the transmittance of knowledge. Naturally,thus invites scrutiny, especially given the context of Hassan being a creative himself, with such a standing (as a literary critic and creative writer) thefunction that immediately springs to mind is whether Hassan heeds his own callIn the light, this article will analyse one of Hassan's works based on his ownanalytical framework--Persuratan Baru--in an effort to determine whether thecontruction of said work truly takes into account his own identification of thefunction of literary works, that is as a medium of knowledge. Hassan's novelPujangga Melayu (1997) will be the study material, with the employment ofthe anlytical framework of Persuratan Baru. By using Persuratan Baru whichdistinguishes between 'knowledge' (ilmu) and 'narrative' (cerita) as an analytical frame work, my findings answer the question brought up earlier that Hassanhas indeed practiced what he has preached, by presenting Pujangga Melayu asa contens manifestation of his literary notion Persuratan Baru'.